Molecular Epizootiology of Rodent Leishmaniasis in a Hyperendemic Area of Iran - AA Akhavan; MR Yaghoobi-Ershadi; H Mirhendi; MH Alimohammadian; Y Rassi; N Shareghi; R Jafari; MH Arandian; H Abdoli; M Ghanei; N Jalali-zand; A Khamesipour (Tehran University of Medical Sciences, 2010)
Background: Zoonotic cutaneous leishmaniasis (ZCL) is an expanding disease and public health problem in Iran. In the current study, natural Leishmania infection rate and seasonal fluctuation of the infection in Rhombomys opimus population of a hyperendemic focus of ZCL in Iran was investigated. Methods:  The study was conducted from October 2006 to October 2008 in Esfahan Province, central part of Iran. An extensive sampling of rodents using Sherman traps was done in different seasons. Nested PCR assay was used for detection and identification of Leishmania species and the results were confirmed using PCR-RFLP. Results: Leishmania infection rate was 58.6% (34 of 58) using nested PCR. 44.8% of the gerbils were infected only with L. turanica and 1.7% with L. gerbilli alone. A mixed natural infection with L. major and L. turanica was seen in 12.1% of the rodents. L. major infection alone was not seen in R. opimus population in the study area. The highest and lowest Leishmania infection rates were observed in fall and spring respectively. L. turanica infection was observed throughout the year whereas mixed infections with L. major and L. turanica was not seen in spring. Conclusion: It is concluded that in the study area, L. major, L. gerbilli and L. turanica circulate in the population of R. opimus. Leishmania major infection usually accompanied by L. turanica in naturally infected gerbils with the highest rate in fall.  It is recommended that the role of L. turanica in the epidemiology and transmission of ZCL be revisited.